ANALISIS KINERJA PROTOTIPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO TURBIN KAPLAN SUMBERDAYA HEAD POTENSIAL - Syarif, Aida (Politeknik Negeri Sriwijaya, 2018)
Research on Prototype of Microhydro Power Plant Kaplan Turbine Potential Head Resource laboratory scale by utilizing potential energy of water and using application on Kaplan Turbine.Performance Analysis Prototype of Micro Hydro Power Plant uses the basic equations that is applied in the calculation analysis to determine the best performance analysis of the generating power of 8.5 watts is located at of head 1.8 m by opening full valve or flow rate variation of 140.5 L/min Minute with number of 16 blades. The results of optimum performance analysis of the plant are on different altitudes of head 1.7 m by opening valve ¾ or a flow rate variation of 105.4 L/min obtained best performance in actual condition with electrical powerperformance of 6.4 watt. The electrical power got best performance at different of head 1.6 m by opening valve ¼ or flow rate variation of 32.8 L/min with the result of 1.1 watt. The electrical power performance shows best performance in head different of 1.4 m by opening valve ½ or 60.8 L/min flowrate variation with the result of 4 watt